Etiology of Nasal Bone Fracture: A Retrospective Analysis of 1, 441 Patients in China. Issue 4 (2nd June 2022) - Zhang, Pu; Zhao, Jing; Zang, Meirong; Gao, Haitao; Wang, Xin; Mu, Junshang
Abstract : Abstract: Nasal bone fracture is the most common injury in the craniofacial area. Understanding the etiology of nasal bone fracture is important for the development of preventive public health programs. In this study, the authors retrospectively examined medical records to extract information about sex, age, injury time, injury cause, occupation, and place of residence (urban or rural) from 1441 patients with nasal bone fracture to investigate the etiology of nasal bone fracture in China. Among the 1441 patients, the ratio of males to females was 3.4:1. The mean patient age was 29.25 years. The most common occupation was student (31.02%). Violence was the most common cause of injury in male patients (35.82%), whereas slip-and-fall accidents were the most common cause in female patients (32.11%). Violence was the most common cause of injury in both urban and rural patients, and 74.19% were attacked by others without a weapon. This report provides important data about the etiology of nasal bone fracture in China and will help improve nasal bone fracture prevention measures.